2014
DOI: 10.1016/j.aller.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The self-reported density of truck traffic on residential streets and the impact on asthma, hay fever and eczema in young adolescents

Abstract: The findings suggest an aggravating effect of truck traffic on current asthma symptoms, but not on asthma, allergic rhinitis and eczema diagnoses. It seems that it probably has an impact as a direct respiratory irritant in early adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Moreover, the frequency of all the health outcomes presented in Table 2 was higher in those adolescents who lived close to a main road or a road with a high density of traffic intensity. These results are consistent with earlier data from the Upper Silesian region [21], as well as with other published observations, where self-reported data of exposure to traffic-related air pollution were also used [38][39][40][41][42].…”
Section: Resultssupporting
confidence: 93%
“…Moreover, the frequency of all the health outcomes presented in Table 2 was higher in those adolescents who lived close to a main road or a road with a high density of traffic intensity. These results are consistent with earlier data from the Upper Silesian region [21], as well as with other published observations, where self-reported data of exposure to traffic-related air pollution were also used [38][39][40][41][42].…”
Section: Resultssupporting
confidence: 93%
“…The results indicated that gas cooking was, in itself, associated with the onset of nasal symptoms in young children, rather than with the other respiratory symptoms examined. Regarding the exposure to external pollution (determined by the frequency of passing trucks on the street) Vlashki et al [10] found a positive association between the frequency of passing trucks on the street and the occurrence of wheezing, dry night cough, symptoms of allergic rhinitis, and rash followed by itching in young adolescents. In our study, in 19 of all 30 children with allergic rhinitis, trucks sometimes passed on the street during the working days.…”
Section: Discussionmentioning
confidence: 99%
“…Direct exposure to environmental air is an additional source of ROS exposure that is unique to the airways. Exogenous sources include: cigarette smoke [6,7], passive smoking [8], gas cooking [9], external pollution, i.e., passing trucks on the street of residence [10] and polluted air, containing ozone [11].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one study in Croatia has reported epidemiological factors associated to eczema in the Balkan area in adolescents 10 . Another one focused on the association of traffic pollution with allergic diseases 11 .…”
Section: Introductionmentioning
confidence: 99%